2015
DOI: 10.1186/s12913-015-1008-8
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the availability, prices and affordability of essential medicines in Jiangsu Province, China

Abstract: BackgroundField surveys conducted in China before the implementation of the essential medicine policy showed that Chinese individuals faced less access to essential medicines. This paper aims to evaluate the availability, prices and affordability of essential medicines in Jiangsu Province, China after the implementation of the policy in 2009.MethodsA cross-sectional survey was conducted in Jiangsu in 2013 using the World Health Organization/Health Action International (WHO/HAI) methodology. Data on the availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 7 publications
7
46
1
Order By: Relevance
“…Similar results were reported in other parts of China, including Shandong, Gansu, Hubei, and Shannxi, with availability of 25%, 33%, 38.9%, and 26.5%, respectively . Conversely, a study conducted in Jangsu province (one of the provinces with the highest economic level in China) showed high availability of EMs (LPG) at public primary hospitals . There are several possible reasons for this.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Similar results were reported in other parts of China, including Shandong, Gansu, Hubei, and Shannxi, with availability of 25%, 33%, 38.9%, and 26.5%, respectively . Conversely, a study conducted in Jangsu province (one of the provinces with the highest economic level in China) showed high availability of EMs (LPG) at public primary hospitals . There are several possible reasons for this.…”
Section: Discussionsupporting
confidence: 73%
“…14,21,22 Conversely, a study conducted in Jangsu province (one of the provinces with the highest economic level in China) showed high availability of EMs (LPG) at public primary hospitals. 23 There are several possible reasons for this. First, during the province-wide centralized bidding for EMs, some manufacturers find themselves in vicious competition with each other, causing the bid price to be lower than the cost price.…”
Section: Discussionmentioning
confidence: 99%
“…However, providers' accounts suggested that financial considerations in different healthcare institutions were not in line with the policies' focus, with evidence that making profits from antibiotic prescriptions was still regarded as a factor related to the use of antibiotics in CHIs. These findings are similar to studies undertaken in various provinces in China, which noted that the EDL and ZMU policies had no effect on the inappropriate use of antibiotics among primary care institutions [52][53][54], even in the period after the introduction of 2011 reform [51,55,56].…”
Section: Discussionsupporting
confidence: 78%
“…However, only a few participants pointed to the influence of finance-related policies (the EDL and ZMU policies), even though this set of policies is one of five priorities of 2009 reform [33]. Moreover, a key aim of this set of policies is to reduce financial incentives from prescribing unnecessary drugs at primary care level, with the expectation that the policies will be implemented in other healthcare institutions, such as tertiary hospitals [49,51]. However, providers' accounts suggested that financial considerations in different healthcare institutions were not in line with the policies' focus, with evidence that making profits from antibiotic prescriptions was still regarded as a factor related to the use of antibiotics in CHIs.…”
Section: Discussionmentioning
confidence: 99%
“…3 There are few studies aimed at evaluation of access to essential medicines in Primary Health Care (PHC) in Brazil 2 and in other countries such as Saudi Arabia 4 and China. 5 Those surveys evaluated the availability dimension with data collected invisits to facilities without an analysis of yearly availability and accessibility. The present study was aimed at evaluating yearly availability and accessibility to medicines in PHC in Northeast Health District of Belo Horizonte, Minas Gerais, Brazil.…”
Section: Introductionmentioning
confidence: 99%